Overcoming the challenges of moving from ISO/TS 16949 to IATF 16949: recommendations for implementing a quality management system in automotive companies - Bozola, Patrícia Maria [UNESP]; Nunhes, Thais V. [UNESP]; Barbosa, Luís César Ferreira Motta; Machado, Marcio C.; Oliveira, Otavio José [UNESP] (Emerald, 2022)
Purpose: In 2016, the ISO/TS 16949 quality management standard for the automotive industry evolved to IATF 16949. The update brought new requirements that need to be analyzed before being implemented in organizations. Therefore, the purpose of this article is to propose guidelines to assist organizations in the automotive sector in the implementation of the elements added in the update to the IATF 16949 standard. Design/methodology/approach: To fulfill this objective, the identification and analysis of the elements added in the evolution from ISO/TS 16949 to IATF 16949 was carried out, and four case studies were conducted in Brazilian automotive companies. Findings: The main elements added to IATF 16949 with the update of the standard are the use of process failure mode effects analysis (PFMEA) for risk analysis; the development of a communication channel for employees to report cases of misconduct and non-conformities; procedures for controlling repaired/reworked products and temporary changes; and the inclusion of autonomous maintenance for the full implementation of total productive maintenance (TPM). Originality/value: The main practical implication/contribution of the research is the proposed guidelines, which can support managers and automotive companies that want to implement, or will go through, the IATF certification process. The article's originality lies in the combination of a theoretical framework and case study analyses to develop the guidelines.
Keywords: Automotive industry; Brazil; IATF 16949; ISO 9001; ISO/TS 16949; Quality management systems